Effect of Petroleum Ether Extract of Kigelia africana Leaf on Serum Lipid Profile in Phenyl hydrazine Induced Anaemic Female Wistar Rats - O, Wilson A.; I, Nnamani V.; O, Agbo E.; O, Ugbada M.; J, Enyam; O, Emuru E.; K, Dasofunjo; C, Uduogu S. (Darul Yasin Al Sys, 2025)
This research was designed to evaluate the effect of petroleum ether extract of Kigelia africana leaf on lipid profile following phenylhydrazine induced anaemia in male Wistar rats. A total of 35 male rats were distributed into five (5) groups of seven (7) rats each per group and experimental Group A served as Normal control (non-anaemic control), group B: Anaemic rats (induced with phenyl hydrazine) without treatment (anaemic control), group C; anaemic rats treated with feroton (Standard control), group D; Anaemic rats with 100mg/kg petroleum ether leaf extract Kigelia africana extract (PETLETKG1), and group E; Anaemic rats treated with 200mg/kg between petroleum ether leaf extract Kigelia africana extract (PETLETKG2). All administrations were done orally using oropharyngeal cannula once per day for 14days (2 week). Blood was collected by cardiac puncture using disposable syringe and needle to draw blood into plane sterile tubes. Thereafter, the samples were analysed using standard methods. The result depicts the significant (p<0.05) increase in serum triglyceride, high density lipoprotein and total cholesterol when compared with both normal and standard control following phenyl hydrazine induced anaemia. More so, the petroleum ether extract of K. africana significantly (p<0.05) decrease on serum low density lipoprotein when compared with both the standard and normal control. The result suggests that the extract might contain some bioactive ingredients or phytonutrients which may reduce or inhibits predisposition to complication(s) associated with cardiovascular related disorders under prolonged anaemic condition.